Highly sensitive sites for guanine-O6 ethylation in rat brain DNA exposed to N-ethyl-N-nitrosourea in vivo. - Nehls, P (1984)
Brain chromosomal DNA isolated from fetal BDIX-rats 1 h after i.v. administration of the ethylating N-nitroso carcinogen N-ethyl-N-nitrosourea (75 micrograms/g body weight), statistically contained one molecule of O6-ethyl-2'-deoxyguanosine (O6-EtdGuo) per 81 micron of DNA, as determined in enzymatic DNA hydrolysates by competitive radio-immunoassay using a high-affinity anti-(O6-EtdGuo) monoclonal antibody (ER-6). After fragmentation of the DNA by the restriction enzyme AluI (average fragment length, Lav = 0.28 micron = 970 bp; length range, Lr = 1.87-0.02 micron = 6540 - 60 bp), a small (approximately 2%) fraction of DNA enriched in specific polypeptides tightly associated with DNA was separated from the bulk DNA by a glass fiber binding technique. As analyzed by immune electron microscopy, approximately 1% of the DNA molecules in this fraction contained clusters of 2-10 (O6-EtdGuo)-antibody binding sites (ABS). On the cluster-bearing fragments (Lav, 0.85 micron +/- 0.50 micron S.D.; corresponding to 2970 +/- 1760 bp) the average ABS-ABS interspace distance was 110 nm (= 390 bp; range approximately 9-600 nm), indicating a highly non-random distribution of O6-EtdGuo in target cell DNA.